Structural, capacitive and energy characteristics of electrochemical electrodes based on polyaniline/multi-walled carbon nanotube nanocomposites - N. A. Davletkildeev; I. A. Lobov; A. O. Nikiforova; D. V. Sokolov (Омский научный вестник)
Polyaniline nanocomposites with nitrogen-doped multiwalled carbon nanotubes, initial and functionalized argon ions are prepared by the in-situ chemical oxidative polymerization of aniline. The morphology of obtained nanocomposites are studied by microscopic methods. The capacitive and energy characteristics of electrochemical electrodes formed by pressing nanocomposites have been studied by cyclic voltammetry. It is shown that an electrode based on a nanocomposite with functionalized nanotubes has the highest specific capacity and energy due to the high porosity of the surface. However, the low mechanical strength of this electrode leads to a decrease in its cyclic stability.